2020
DOI: 10.1088/1742-6596/1629/1/012081
|View full text |Cite
|
Sign up to set email alerts
|

Internal control quality, equity pledge financing and investment efficiency

Abstract: In the present situation of difficult enterprise-financing, the equity pledge of corporate controlling shareholders is a effective channel for enterprises to relieve financing constraints. Whether an enterprise can formulate a reasonable investment policy to obtain investment income effectively and achieve financial goals, determines whether an enterprise can develop in the long-tern future. The target of this paper is to approach how the investment efficiency of an enterprise will change with the increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Meanwhile, some scholars believe that investment decisions are not only related to whether the company has equity pledging, but are also affected by the proportion of the equity pledge. Mu, Zhou, and Cao (2020) found that a company's investment decisions are highly correlated with the equity pledge ratio. Companies with low equity pledge ratios invest in operating activities to improve performance, and companies with high equity pledge ratios may adopt short-term investment strategies, such as financial investment, in order to prevent the transfer of control, with high returns and quick results.…”
Section: Equity Pledges and Corporate Investmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, some scholars believe that investment decisions are not only related to whether the company has equity pledging, but are also affected by the proportion of the equity pledge. Mu, Zhou, and Cao (2020) found that a company's investment decisions are highly correlated with the equity pledge ratio. Companies with low equity pledge ratios invest in operating activities to improve performance, and companies with high equity pledge ratios may adopt short-term investment strategies, such as financial investment, in order to prevent the transfer of control, with high returns and quick results.…”
Section: Equity Pledges and Corporate Investmentmentioning
confidence: 99%
“…Ke, Li, and Wu (2019) studied the types of corporate equity pledge affecting corporate investment behavior and found that the proportion of the equity pledge does not have a simple linear relationship with company investment, which shows that the controlling shareholders with different proportions of equity pledge adjust the company's investment strategy for different reasons. In order to prevent the transfer of shareholders' control, two types of inefficient investment-over-investment and under-investment-may result when the controlling shareholders make and implement investment decisions in the company (Mu et al, 2020). Moreover, risk tolerance affects investment efficiency, and the reduction of risk tolerance and equity pledging will inhibit risk investment.…”
Section: Equity Pledges and Corporate Investmentmentioning
confidence: 99%
“…In the early literature on overinvestment, most of them were based on principal-agent theory, and did not pay attention to the impact of managers’ own irrational behavior on the investment decision and development of enterprises. Mu et al (2020) found that overconfident managers lack the ability to rationally analyze, and often misjudge the project’s net present value and rate of return, resulting in overinvestment. In addition, considering the effect of manager gender on this relationship, the overinvestment caused by overconfidence of male managers will be more serious ( Liu, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The existence of different industries represents the existence of different corporate business philosophy and commitment to environmental protection. Heavy-pollution industry is a kind of high energy consumption, high-pollution industry, and fulfilling environmental responsibility is the key to improve environmental quality [86][87][88][89][90]. In order to study the impact of different industry types on government environmental subsidies and enterprise environmental performance, this paper divides the empirical samples into two types, conducts multiple regression analysis, and obtains different results.…”
Section: Industrial Difference Regression Analysismentioning
confidence: 99%